2014
DOI: 10.1038/cddis.2014.130
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181a-mediated downregulation of AC9 protein decreases intracellular cAMP level and inhibits ATRA-induced APL cell differentiation

Abstract: AC9 is one of the adenylate cyclase (AC) isoforms, which catalyze the conversion of ATP to cAMP, an important second messenger. We previously found that the integration of cAMP/PKA pathway with nuclear receptor-mediated signaling was required during all-trans retinoic acid (ATRA)-induced maturation of acute promyelocytic leukemia (APL) cells. Here we showed that AC9 could affect intracellular cAMP level and enhance the trans-activity of retinoic acid receptor. Knockdown of AC9 in APL cell line NB4 could obviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Two of the 4 genes (ADCY9 and ONECUT2) were expressed at significantly higher levels in mesenchymal than in epithelial KP cell lines (Supplemental Figure 7A). Activities of reporters driven by the 3′-UTRs of ADCY9 or ONECUT2 were lower in miR-181b-transfected 344SQ cells than in negative control transfectants, and loss of the miR-181b-binding sites in the ADCY9 and ONECUT2 3′-UTRs ablated the miR-181b-induced suppression of both reporters (Figure 5B), which is consistent with a prior report on ADCY9 (27).…”
Section: Resultssupporting
confidence: 81%
“…Two of the 4 genes (ADCY9 and ONECUT2) were expressed at significantly higher levels in mesenchymal than in epithelial KP cell lines (Supplemental Figure 7A). Activities of reporters driven by the 3′-UTRs of ADCY9 or ONECUT2 were lower in miR-181b-transfected 344SQ cells than in negative control transfectants, and loss of the miR-181b-binding sites in the ADCY9 and ONECUT2 3′-UTRs ablated the miR-181b-induced suppression of both reporters (Figure 5B), which is consistent with a prior report on ADCY9 (27).…”
Section: Resultssupporting
confidence: 81%
“…sAC inhibition could be a strategy to achieve the elusive goal of a male contraceptive (Roth and Amory, 2016), but the proposed broad expression and function of sAC beyond the male reproductive system (Steegborn, 2014;Levin and Buck, 2015) would probably result in many side effects. It remains to be determined whether the recently introduced microRNA approach (Zhuang et al, 2014) constitutes a clinically useful approach to target mACs.…”
Section: Discussionmentioning
confidence: 99%
“…Reports for AC9 knockout phenotypes are lacking. However, microRNAs targeting AC9 (miR-142-3p, miR-181a, and miR-181b) point to a decrease in AC9 expression in sepsis (Risoe et al, 2011) and potential roles in regulating cell proliferation in cervical cancer cells and differentiation of promyelocytic leukemia Zhuang et al, 2014). Several reports suggest roles for AC9 in immune function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs (miRNAs or miRs) are a class of endogenous, non-coding, small, single-stranded RNAs consisting of 18-25 nucleotides, which mediate the post-transcriptional regulation of target genes via inhibiting translation or inducing RNA degradation (5,6). Increasing evidence has demonstrated that miRNAs can function as oncogenes or tumor suppressor genes in cancer, and can suppress cell signaling pathways to modulate various cancer cell processes, including cell proliferation, apoptosis, differentiation and migration (7,8). The ectopic expression of miRNAs is key in the development of LSCC (9), and certain miRNAs directly modulate the apoptosis, proliferation and invasion of LSCC cells (3,10).…”
Section: Introductionmentioning
confidence: 99%